2017
DOI: 10.1002/bit.26447
|View full text |Cite
|
Sign up to set email alerts
|

Power input effects on degeneration in prolonged penicillin chemostat cultures: A systems analysis at flux, residual glucose, metabolite, and transcript levels

Abstract: In the present work, by performing chemostat experiments at 400 and 600 RPM, two typical power inputs representative of industrial penicillin fermentation (P/V, 1.00 kW/m 3 in more remote zones and 3.83 kW/m 3 in the vicinity of the impellers, respectively) were scaled-down to bench-scale bioreactors. It was found that at 400 RPM applied in prolonged glucose-limited chemostat cultures, the previously reported degeneration of penicillin production using an industrial Penicillium chrysogenum strain was virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
3
22
0
Order By: Relevance
“…In the reference chemostat cultures, the extracellular C s remains at the level of 2.6 ÎŒM over 250 h, and this agrees with the glucose uptake kinetics (Wang et al ., ), giving a high glucose affinity of about 5 ÎŒM, in reasonable accordance with the 7.8 ÎŒM as reported by de Jonge et al . ().…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…In the reference chemostat cultures, the extracellular C s remains at the level of 2.6 ÎŒM over 250 h, and this agrees with the glucose uptake kinetics (Wang et al ., ), giving a high glucose affinity of about 5 ÎŒM, in reasonable accordance with the 7.8 ÎŒM as reported by de Jonge et al . ().…”
Section: Resultssupporting
confidence: 52%
“…This system remains in the limitation regime. An explanation is that in this experiment there is an interference with the liquid circulation time of about 1–2 s (Wang et al ., ), which is close to the feed switch‐on time interval (3 s) of the 30 s IFR. The maximum feast glucose concentrations in 30 s, 3 min and 6 min IFR experiments are 30, 167 and 333 ÎŒM (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As an example, as shown in Figure , our research group has developed and validated standard operating procedures (SOPs) for fast sampling, quenching, and efficient extraction of metabolites as well as preparation of U‐ 13 C metabolites as internal standards from P. chrysogenum to allow for global analysis of the metabolome under both steady‐state and nonstationary conditions (Wang, Chu, et al, ). This protocol has been exactly followed in our previous studies, which delivered invaluable information for in silico metabolic modeling and revealed regulatory mechanisms in response to genetic or environmental perturbations (Tang et al, ; Wang, Chu, et al, ; Wang, Chu, et al, ; Wang, Wu, et al, ; Wang, Zhao, et al, ; Wang, Zhao, et al, ).…”
Section: Quantitative Metabolomics and Its Application In Systems Metmentioning
confidence: 99%
“…Typically, by applying different feeding strategies (e.g., intermittent feeding, stochastic feeding; de Jonge et al, ; Delvigne, Destain, & Thonart, ; Delvigne, Lejeune, Destain, & Thonart, ; Wang, Zhao, et al, ) or scale‐down simulators (Neubauer & Junne, ; Wang et al, ), spatially nonhomogeneous environments encountered by cells in large‐scale fermentors can be mimicked at laboratory‐scale bioreactors. Recent studies have shown that before industrial scaling‐up, scaling down industrial‐scale fermentation processes can gain deep insights into the interaction between metabolic dynamics and hydrodynamics in industrial‐scale fermentation processes (Buchholz et al, ; Haringa et al, ; Lemoine et al, ; Lemoine, Maya Martiotanez‐Iturralde, Spann, Neubauer, & Junne, ; Loffler et al, ; Marba‐Ardebol, Bockisch, Neubauer, & Junne, ; Nieß, Löffler, Simen, & Takors, ; Simen et al, ; Spann et al, ; Wang, Wu, et al, ; Wang, Zhao, et al, ). However, it should be noted that a prerequisite for this kind of representative downscaling experiment is the knowledge of how conditions vary in large‐scale reactors.…”
Section: Introductionmentioning
confidence: 99%